2017
DOI: 10.2147/jpr.s126259
|View full text |Cite
|
Sign up to set email alerts
|

Vulvodynia: a consideration of clinical and methodological research challenges and recommended solutions

Abstract: Vulvodynia, an idiopathic chronic vulvar pain, is a prevalent genital pain condition that results in significant impairment to sexual, relational, and psychological functioning of affected women and their romantic partners. Despite its high prevalence, there remain gaps in knowledge and health care access for women coping with vulvodynia, given its varied clinical presentation and no widely accepted treatment protocol. The past several decades have seen important advancements in understanding vulvodynia and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 106 publications
0
15
0
4
Order By: Relevance
“…However, pain reduction does not necessarily improve the mental and sexual well-being of patients with PV. 11 Therefore, we assessed treatment efficacy by evaluating pain reduction and changes in patients’ sexual function and treatment satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pain reduction does not necessarily improve the mental and sexual well-being of patients with PV. 11 Therefore, we assessed treatment efficacy by evaluating pain reduction and changes in patients’ sexual function and treatment satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding measuring the treatment results, there is a wide range of tools for assessing pain in the vestibule, including real-time pain measurements (during a physical test such as the Q-tip test), pelvic floor muscle evaluation by electromyography or ultrasound, or assessing pain based on patient self-reports. 5 , 11 , 12 A review of 25 studies identified 110 different tools. 5 The vast majority of these (86%) relied on participants’ self-reported improvements in their mental state, sexual function, and pain reduction, compared with 12% of the tools that relied on reports by physicians.…”
Section: Discussionmentioning
confidence: 99%
“…W literaturze obowiązuje rekomendacja oceny punktów końcowych w leczeniu bólu przewlekłego, opracowana w 2003 roku -Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT), zalecana także do oceny wyników terapii w Vd [6,[17][18][19]. W IMMPACT zakłada się konieczność oceny sześciu kluczowych parametrów w badaniach klinicznych dotyczących przewlekłego bólu i Vd: ból oceniany w skali NRS, funkcjonowanie fizyczne w tym także seksualne, funkcjonowanie emocjonalne (depresja, lęk), subiektywna ocena przez pacjenta poprawy stanu zdrowia i zadowolenie z leczenia, objawy i zdarzenia niepożądane oraz dyspozycyjność pacjenta w badaniu.…”
Section: Wstępunclassified
“…Nie ma wielu prac, w których oceniano by efekt odległy po leczeniu. "Sukces" terapii w Vd bywa rzadko definio-wany przez badaczy w literaturze [19], niemniej został określony jako punkty końcowe w IMMPACT Consensus Statement w terapii bólu przewlekłego. Przyjmuje się, że redukcja subiektywnych dolegliwości bólowych o 50% lub więcej w NRS stanowi odzwierciedlenie wyraźnej poprawy w odczuciu pacjenta [6,17,18].…”
Section: Dyskusjaunclassified
See 1 more Smart Citation